Degradasi Kandungan Nitrogen Pada Pupuk Organik Cair Selama Dalam Penyimpanan - Nurlaila (Buletin Loupe, 2020)
Liquid organic fertilizer cannot be stored for a long time or the POC will be damaged, indicated by the change in colour and odor. The aim of this research was to analyze the change in nitrogen content in liquid organic fertilizer during storing. The laboratory result was compared to PerMenTan No.70 / Permentan/ Sr.140/10/2011. The research was conducted in Laboratorium Tanah dan Air at Politani Samarinda from January to March 2017. The research started by mixing water hyacinth, mucuna bracteata, goa feces and shrim shell for 28 days. This was followed by observation on physical chenges during storing and analyisng nitrogen content after storing. Nitrogen content in new POC was 0.1918%. After one to six days of storing the nitrogen content was down to 0.0349%. The nigrogen content of POC made by mixing water hyacinth, mucuna bracteata, goat feces and shrimp shell has not met the standard of PerMenTan No. 70/Permentan/Sr.140/10/2011.